Nifedipine, Calcium Channel Blocker (Antihypertensive), as a Tocolytic to inhibit Premature Birth in Reducing the Risk of Neonatal Death in Childbirth: Meta-Analysis and Systematic Review of Large Clinical Trial: Nifedipine, Penghambat Kanal Kalsium (Antihipertensi), sebagai Tokolitik dalam Menghambat Kelahiran Prematur dalam Menurunkan Risiko Kematian Neonatus Pada Persalinan: Meta-Analisis dan Telaah Sistematis dari Studi Besar Uji Klinis - Axel J. Olda; Joue Abraham Trixie; Glenn Bolang; Yoga Rahmat Witular; Saerang Langi (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objective: To evaluate the role of nifedipine as a tocolytic agent.Methods: Literature searches use medical search engines for example Pubmed, Google Scholar and Medical scientific journals, as like the American kind of Journal that is Learning Obstetrics and also learn about Gynecology. The literature used were published from 1986 to 2020. The main data extraction was in the form of an extended gestation period, divided into 48 hours, 7 days, and 37 weeks with data analysis using the RevMan 5.4 application. Result: Twenty-four clinical trials were analyzed with total amount shown of 2,889 study subjects. The purpose of using kind of nifedipine to be such a tocolytic indicates no significant difference, within 48 hours or (RR 1.06; 95% CI, 0.99 - 1.13; p shown = 0.12), 7 days (RR 1.02; 95% CI, 0.95 - 1.09; p = 0.57), and up to 37 weeks (RR 1.22; 95% then CI, 0.96 - 1.54; p = 0.10) at the time it is compared with the group of control.Conclusion: Administration of nifedipine as a tocolytic did not have a statistically significant difference, both in prolonging pregnancy and side effects for pregnant women and neonates compared to the control group.Keyword: meta-analysis, nifedipine, preterm delivery, prolongation pregnancy, tocolytic. Abstrak Tujuan: Untuk mengevaluasi peran nifedipin sebagai tokolitik.Metode: Pencarian literatur menggunakan mesin pencari medis seperti Pubmed, Google Scholar dan jurnal ilmiah medis, seperti American Journal of Obstetrics and Gynecology. Literatur yang digunakan dalam rentang tahun 1986 - 2020. Kata kunci adalah (